Predation on Asian Common Toad (Duttaphrynus melanostictus) by Bengal monitor lizard (Varanus) in National botanical garden, Bangladesh (Bangladesh Journal of Zoology, 2024)
Abstract not availableBangladesh J. Zool. 52(1): 133-137, 2024